INDONESIAN DEFENSE DEGREE STRATEGY FACING THE THREAT OF COVID-19 - Hasto Kristiyanto; Purnomo Yusgiantoro; Amrulla Octavian; I Wayan Midhio (UNIVERSITAS PAKUAN, 2021)
National defense is faced with an uncertain changing strategic environment. For this reason, in order for a country to be able to maintain the sovereignty and security of its people, a state defense strategy strategy is needed that is adaptive to all changes and potential threats. The strategy of holding power during the COVID-19 pandemic is different from previous conditions. This study focuses on developing a strategy for deploying defense forces that are appropriate to deal with all these threats. The research uses qualitative methods with data collection techniques from literature studies. The results of the study prove that the concept of a grand strategy which is a universal defense system has principles that are suitable for dealing with increasingly complex threats in the future.